FUZZY SP-IRRESOLUTE MAPPING - Krsteska, Biljana (Matematichki Bilten, 1997)
The aim of this paper is to introduce the fuzzy SP-irresolute continuous, fuzzy SP-irresolute open and fuzzy SP-irresolute closed mappings. Also we establish some of their characteristic properties.